Guest editorial Special issue on visualization and computer graphics. - Liu, Shixia (Tsinghua Science and Technology)
In the decade of data explosion, a significant challenge is how to transform data into understandings and insights that are useful to people. Visualization, the use of computer-supported, interactive visual representations of data to amplify cognition[1], is an important approach to addressing this challenge. In particular, scientific visualization primarily represents physical or geometric data while information visualization mainly represents abstract data such as text documents, graphs, and multidimensional data. Visual analytics, springing out of the fields of information visualization and scientific visualization, is an emerging research area that targets analyzing massive amounts of information for timely decision making[2]. Its basic approach is to use interactive visual interfaces to facilitate analytical reasoning so that human perception abilities and domain knowledge can be exploited together with computational powers. Closely related to visualization, computer graphics is primarily about representation and manipulation of image data by a computer.